Robust predictive control using a time-varying youla parameter - Van Den Boom, Ton J.J.; De Vries, Rob A.J. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a standard predictive control problem (SPCP) is formulated, which consists of one extended process description with a feedback uncertainty block. The most important finite horizon predictive control problems can be seen as special realizations of this SPCP. The SPCP and its solution are given in a state-space form.
Keywords: predictive control; Youla parametrization; stability; robustness